ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN PENGGUNAAN DANA CSR OLEH PERTAMINA FOUNDATION DALAM PROGRAM INSPIRASI INDONESIA TIMUR - WICAKSONO, OKTIAFERY (Jurnal Akuntansi AKUNESA, 2015)
This Research aims to determine the application of the internal control system by Pertamina Foundation In The Eastern Indonesia Inspiration Program and its conformance to the latest 2013 COSO. The latest COSO 2013 includes five components of internal control systems that have been developed into 17 principles and 77 the focal point. The source data used in the study is data on policies, procedures and implementation of internal control systems. The result of this study indicates Pertamina Foundation has implemented 94.12% of the principles of the latest 2013 COSO internal control system. The principle that is not conducted yet is the organization principle of selecting and developing the general control over technology to support achievement of the objectives. We recommend that there should be a development of technologies so that administration process can be done quickly.Keyword: Internal Control System, Corporate Social Responsibility, COSO 2013